2020
DOI: 10.1111/ene.14252
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of death associated with the use of proton‐pump inhibitors in patients with dementia and controls – a pharmacoepidemiological claims data analysis

Abstract: Background and purpose The use of proton‐pump inhibitors (PPIs) was reported to be associated with increased mortality risk and has been proposed as a potential risk factor for neurodegenerative diseases. We aimed to assess the impact of PPI use on survival in patients with dementia as compared with controls. Methods This register‐based control‐matched cohort study included 28 428 patients with dementia ascertained by the prescription of antidementia drugs and two contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Although usually considered safe, these drugs have been associated with increased risks of side effects such as bone fractures, kidney disease, microscopic colitis, and hypomagnesaemia [14]. Furthermore, the long-term use of PPIs was recently reported to be associated with an increased mortality risk [4], and an increased dementia risk [9]. PPIs decrease intracellular pH and increase the extracellular pH via inhibition of vacuolar H + -ATPases (V-ATPases) in a covalent interaction [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although usually considered safe, these drugs have been associated with increased risks of side effects such as bone fractures, kidney disease, microscopic colitis, and hypomagnesaemia [14]. Furthermore, the long-term use of PPIs was recently reported to be associated with an increased mortality risk [4], and an increased dementia risk [9]. PPIs decrease intracellular pH and increase the extracellular pH via inhibition of vacuolar H + -ATPases (V-ATPases) in a covalent interaction [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find an association between PPI use and ALS risk in the present study, the role of PPIs on the survival of ALS patients needs to be studied further. A study of US veterans found an increased mortality among PPI users 28 , and a more recent study from Austria reported an increased mortality risk associated with PPI use among dementia patients and controls 29 . In terms of ALS, only one study examined the effect of various medications including PPIs on the disease course and failed to show a statistically significant relationship between PPIs and ALS survival after correction for multiple testing 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although usually considered safe, these drugs have been associated with increased risks of side effects such as bone fractures, kidney disease, microscopic colitis, and hypomagnesaemia. 14 Furthermore, the longterm use of PPIs was recently reported to be associated with an increased mortality risk, 16 and an increased dementia risk. 17 PPIs decrease intracellular pH and increase the extracellular pH via inhibition of vacuolar H + -ATPases (V-ATPases) in a covalent interaction.…”
Section: Discussionmentioning
confidence: 99%